Habitat-associated detection of Toxoplasma gondii and Sarcocystis spp. in Cetaceans from the Brazilian coast - Thalita Faita; Lara Borges Keid; Natalia Silvestre-Perez; Gláucia Pereira de Sousa; Geovana Carolaine Ramos Thomé; Beatriz de Magalhães Ceron; Samira Costa-Silva; Cristiane Kiyomi Miyaji Kolesnikovas; Pedro Volkmer de Castilho; Fernanda Loffler Niemeyer Attademo; Fábia de Oliveira Luna; Angélica Maria Sánchez-Sarmiento; et al. (Veterinary Research Communications, 2026)
Cetaceans are sentinels of marine ecosystem health and are increasingly exposed to protozoal pathogens. This study investigated the occurrence and molecular identity of Sarcocystidae protozoa in 159 stranded cetaceans representing 21 species along the Brazilian coast. Molecular analysis based on PCR amplification and sequencing of the sarcocystid internal transcribed spacer 1 (ITS1) region revealed infections in 14 individuals, showing a clear habitat-associated distribution. Toxoplasma gondii and Sarcocystis neurona were detected in nine coastal cetaceans, consistent with transmission from terrestrial definitive hosts via land-to-sea runoff. In contrast, a distinct Sarcocystis lineage consistently reported in cetaceans and pinnipeds was identified in six pelagic individuals. Analyses of mitochondrial cytochrome c oxidase subunit I and 18S rDNA markers revealed close similarity to species reported in avian definitive hosts, suggesting a life cycle involving marine or pelagic birds. This ecological segregation reflects differences in parasite transmission pathways and host–habitat interactions. This study provides the first report of S. neurona in Brazilian cetaceans and the first global record of this parasite in Guiana dolphin ( Sotalia guianensis ). Overall, these findings emphasize the role of habitat use in shaping infection patterns and reinforce the importance of a One Health framework to understand land–sea and potentially marine-specific pathogen transmission, as well as its implications for marine wildlife health and conservation.

Desertification reshapes soil fungal community structure across Brazilian dryland ecoregions - Ruggeri M.M. Santos; Katriny K.S. Negreiros; Ademir S.F. Araujo; Erika V. de Medeiros; George R. Lambais; Rodrigo S. Macedo; Raphael M. Beirigo; Diogo P. Costa; Kaio G.V. Garcia; Antonio Y.V. Lima; Gabriel N. Nóbrega; Lucas W. Mendes; et al. (Applied Soil Ecology, 2026)

Celtis guatemalensis (Cannabaceae: Celtis subg. Celtis), a new tree species from the highlands of Guatemala, with an updated key for Celtis of Mexico and Central America - Knut Eisermann; Henrique Borges Zamengo; Débora Cintia Chamorro; Claudia Avendaño-Mendoza; Rodrigo Faleiro de Lima; Ana Barrios; Luis Javier Aju; Sofía Cabañas (Kew Bulletin, 2026)

Hydroxyapatite and cobalt ferrite composites as ciprofloxacin release systems for the treatment of osteomyelitis – An experimental study - Cristiane Carneiro Vital Cintra; Dayana Alersa Ferreira Ermita; Gabriela Castro Lopes Evangelista; Rafael Colman Cardoso; Rodrigo Viana Sepúlveda; Emily Correna Carlo Reis; Fabrício LucianiValente; Carlos Eduardo Pereira; Raffaella Bertoni Cavalcanti Teixeira Santos; Andréa Pacheco Batista Borges (The Veterinary Journal, 2026)

Modulating Gallotannin Bioavailability with Tannase-Treated Sumac Tea and Lactobacillus Plantarum: Effects on Inflammation and Cognitive Function - A1344 - Susanne U. Talcott; Elizabeth U. Culpepper; Larissa U. Borges; Rodrigo U. San Cristobal Blanco; Tara U. Mahmood; Stephen Talcott (Journal of Nutrition Education and Behavior, 2026)

Long‑term impacts of a composted sewage sludge–based Class B organic fertilizer on soil micronutrients and crop production in the Tropics - Luana Corrêa Silva; Aline Renée Coscione; Rodrigo Silva Alves; Philippe Solano Toledo Silva; Adrielle Rodrigues Prates; Leiliane Dutra Silva; Fabrício da Silva Vasconcelos; Jussara Borges Regitano; Cassio Hamilton Abreu-Junior; Wanderley José de Melo; Gian Franco Capra; Arun Dilipkumar Jani; et al. (European Journal of Agronomy, 2026)

Genotoxicity and oral tissue damage associated with tooth bleaching agents: A scoping review - Patrick Wesley Marques de Boa; Mariana Silva de Bessa; Flávio Pereira dos Santos Filho; Lara Beatriz Nascimento Diniz; Rodrigo Othávio de Assunção e Souza; Laércio Almeida de Melo; Arthur Cesar de Medeiros Alves; Boniek Castillo Dutra Borges (Mutation Research - Reviews in Mutation Research, 2026)

Microplastics as stratigraphic tracers of post-1950 deposition in a reworked tropical estuary, Brazil - Priscila Bassi Penteado; Rodrigo Esteves Rocha; Wanilson Luiz-Silva; Alfredo Borges de-Campos (Regional Studies in Marine Science, 2026)

Laboratory and field evaluation of LAMP assays for canine visceral leishmaniasis diagnosis - Geovanna Vioti; João Augusto Franco Leonel; Trícia Maria Ferreira de Sousa Oliveira; Diogo Tiago da Silva; Maria Luana Alves; Andrea Cristina Higa Nakaghi; Lara Borges Keid; Luiz Ricardo Paes de Barros Cortez; Thayssa Duarte Costa; Rodrigo Martins Soares (Research in Veterinary Science, 2026)

Effect of a multivalent vaccination protocol on reproductive efficiency in Bos indicus beef females - Rodrigo de Morais; Fúlvio Picanço Florenzano; Adryele Araujo Borges Lima; Giovanna Meireles Borges; Sacha Manuelly da Silva Lobato; Daniel Rocha de Oliveira; Lorrayne Honorio de Paula; Weslen Fabricio Pires Teixeira; Moyses dos Santos Miranda; Rinaldo Batista Viana; Bruno Moura Monteiro (Animal Reproduction Science, 2026)

Dominant effects of the antiepileptic drug carbamazepine over climate change stressors on Mytilus galloprovincialis toxicity - Farhat-Un-Nisá N. Bajwa; Marta Cunha; Juliano M. Vilke; Bruno D.D. Fragoso; Rodrigo Borges; Amadeu M.V.M. Soares; Rosa Freitas; Tainá G. Fonseca (Marine Pollution Bulletin, 2026)

Alternative strategic control of Rhipicephalus microplus in the Cerrado of Minas Gerais, Brazil, by exploiting abiotic conditions - Vinicius da Silva Rodrigues; Maria Clara Oliveira Sousa; Rodrigo da Costa Maia; Giovanna Cirqueira Ribeiro Borges; Amanda Ferreira Rezende; Ana Carolina Sousa; Gustavo Martins Felix Silva; Adriane Suzin; Matheus Augusto Ferreira Fernandes; Matias Pablo Juan Szabó (Veterinary Parasitology, 2026)

Effects of caffeic acid phenethyl ester on cell death and survival pathways in human osteosarcoma cells - Bianca Leme; Luis Francisco Borges da Silva; Adriano de Souza Pessoa; Flávia Godoy Iano; Emanuelle Pangoni de Carvalho; Laura Ribeiro; Valdecir Farias Ximenes; Rodrigo Cardoso de Oliveira (Natural Product Research, 2026)

Postharvest nitric oxide treatment to long shelf life tomatoes: Impact on the metabolism, skin color, overall quality, and volatile compound profile - Fabio Rodrigo Thewes; Bruna Regina Carvalho Pinto; Guilherme Zanon Peripolli; Kaliandra Zottele Nunes; Mateus Gaiardo dos Santos; Francieli Ullrich; Natiéli Wollmann Schutz; Lilian Osmari Uhlmann; Carine Borges Batista; Roger Wagner; Vanderlei Both (Postharvest Biology and Technology, 2026)

Vertical structuring of zooplankton communities during a short-term study in the Bransfield Strait, Antarctica - Letícia Cazarin Baldoni; Raul Rodrigo Costa; Vanessa Ochi Agostini; Carlos Rafael Borges Mendes; Erik Muxagata (Polar Biology, 2026)
Phytoplankton and zooplankton organisms are important constituents of the Antarctic marine food-web and play important roles in carbon export. This study analysed the composition and vertical distribution of zooplankton in association with phytoplankton community composition over a 20 h in February 2017 at a fixed station in the central basin of the Bransfield Strait. The water column was stratified, resulting in the dominance of cryptophytes in phytoplankton community. The zooplankton community showed a vertical distribution patterns linked to water column dynamics and food availability, which led an accumulation of salps at the surface during all sampling periods. Calanoid copepods were the main taxa in deeper layers. The consistent presence of salps at the surface highlights their potential role in shaping community structure. If sustained over longer periods, such dominance may influence trophic pathways and carbon flux by altering grazing pressure on phytoplankton and enhancing vertical carbon export through dense, fast-sinking fecal pellets. These findings contribute to a better understanding of zooplankton vertical distribution over short time periods and underscore the importance of further investigating the ecological implications of salp dominance in Antarctic ecosystems.

Red light–mediated enhancement of the antifungal activity of Physalis angulata against Candida species - Bianca Borges de Alencar; Maria Laura Faleiros Ribeiro de Melo; Wanderson Zuza Cosme; Matheus Henrique Francisco Dias; Camila Cristina Baccetti Medeiros; Rodrigo Sorrechia; Rosemeire Cristina Linhari Rodrigues Pietro; Fabiano Guimarães Silva; Marcio Luís Andrade e Silva; Wilson Roberto Cunha; Patrícia Mendonça Pauletti; Regina Helena Pires; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Evaluation of hair samples for PCR detection of Leishmania infantum in dogs - Geovanna Vioti; João Augusto Franco Leonel; Trícia Maria Ferreira de Sousa Oliveira; Diogo Tiago da Silva; Maria Luana Alves; Andrea Cristina Higa Nakaghi; Lara Borges Keid; Rodrigo Martins Soares (Research in Veterinary Science, 2026)

Phase Separation of Acidogenic and Methanogenic Treatments Mitigates the Ecotoxicity of Sewage Containing Organic Micropollutants - Tallyson Tavares Cunha de Souza; Rodrigo Braz Carneiro; Aline Christine Bernegossi; Gleyson Borges Castro; Mayara Caroline Felipe; Lidia Moura; Álvaro José Santos-Neto; Juliano José Corbi (Water, Air, & Soil Pollution, 2026)

Effects of Treatment with Dexmedetomidine on Neurochemical and Cognitive Alterations Induced by Sepsis in an Animal Model - Mariane Abatti; Luana Cucker; Andriele Vieira; Monique Michels; Amanda Goulart; Heloisa Borges; Rodrigo Dias; Emily Corneo; Diogo Dominguini; Ingrid Farias; Flávio Henrique Reginatto; Cristiane Ritter; et al. (Journal of Molecular Neuroscience, 2025)

1-Butanol applied to ‘Maxi Gala’ apples during postharvest shelf life and after dynamic controlled atmosphere: Effects on metabolism and quality - Barbara Cecconi Deon; Fernanda de Candido de Oliveira; Francis Júnior Soldateli; Carine Borges Batista; Manoela Meira Balzan; Aline de Cássia Machado; Auri Brackmann; Vanderlei Both; Daniel Alexandre Neuwald; Fabio Rodrigo Thewes; Roger Wagner (Postharvest Biology and Technology, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Chronic iron overload disrupts the reproductive tract and leads to infertility: From a clinical case report to the experimental study of reproduction in female mice - Charles S. da Costa; Vinícius Bermond Marques; Jandinay Mageski; Paulo Caleb J.L. Santos; Rodrigo Alves Faria; Isabela V. Sarmento; Poliana Borges de Oliveira; Maira Krause; Maria Tereza W. D Carneiro; Leonardo dos Santos; Jones B. Graceli (Reproductive Toxicology, 2025)

Isolates of Pavonia multiflora as alternative control of the phytopathogen Fusarium solani piperis - Jessyca Aparecida Paes Dutra; Jéssica Raquel Borges Monteiro; Weverson Cavalcante Cardoso; Valdemar Lacerda Júnior; Rita de Cássia Ribeiro Gonçalves; Warley de Souza Borges; Rodrigo Rezende Kitagawa (Phytochemistry Letters, 2025)

Integrated 3D forward stratigraphic and basin modeling of the Santos Basin, offshore Brazil: Implications of sedimentary depositional facies and CO2 migration for silicification of continental carbonate reservoirs - Alina-Berenice Christ; Marie-Christine Cacas-Stentz; Nathalie Collard; Fadi Henri Nader; Elisabeth Bemer; Rodrigo Brandão Bunevich; João Paulo Borges Gomes; Olinto Gomes de Souza; Maria Anna Abreu de Almeida dos Reis (Marine and Petroleum Geology, 2025)

Distribution, composition, and drivers of suspended particulate organic matter in the Gerlache Strait, Northern Antarctic Peninsula - Elis Brandão Rocha; Eunice da Costa Machado; Maurício Garcia de Camargo; Carlos Eduardo de Rezende; Pedro Vianna Gatts; Carlos Rafael Borges Mendes; Raul Rodrigo Costa; Mônica Wallner-Kersanach; Mauricio M. Mata; Rodrigo Kerr (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Cannabidiol potentiates phenobarbital-induced cell death in the developing brain - Rubia Aparecida Fernandes; João Vitor Melo Ribeiro; Rodrigo Espindula Torres; Giovanna Bruno Borges; Larissa Gabrielly Ribeiro de Freitas; Olagide Wagner de Castro; Marcio Flávio Dutra Moraes; Norberto Garcia-Cairasco; Fabrício A. Moreira; Victor Rodrigues Santos (NeuroToxicology, 2025)

The role of phytoplankton in the deep chlorophyll maximum CO2 dynamics along a zonal section (34.5°S) in South Atlantic Ocean - João Vitor Langorte Bueno; Rodrigo Kerr; Andréa da Consolação de Oliveira Carvalho; Carlos Rafael Borges Mendes (Marine Environmental Research, 2025)

The potential of native microalgae consortia to remove pharmaceutical compounds present in treated wastewater - Valdemira Afonso; Brígida Rodrigues; Rodrigo Borges; Raúl Barros; Maria João Bebianno; Sara Raposo (Journal of Environmental Management, 2025)

The Impact of Biological Sex And High-Fat High-Fructose Diet on Brain Dysfunction in an Animal Model of Sepsis - Andriele Vieira; Mariane Abatti; Monique Michels; Amanda Goulart; Cristiano Julio Faller; Heloisa Borges; Filipe Fernandes; Diogo Dominguini; Luana Rocha; Emily Córneo; Rodrigo Dias; Felipe Dal-Pizzol (Molecular Neurobiology, 2025)

Mycoplasma haemofelis and ‘Candidatus Mycoplasma haemominutum’ in domestic cats from Pelotas, RS: molecular detection and risk factors - Paola Renata Joanol Dallmann; Diago Dutra Lima; Alexsander Ferraz; Taise Vencato Isquierdo; Ceres Cristina Tempel Nakasu; Charles Silva de Lima; William Borges Domingues; Leandro Silva Nunes; Antonio Duarte Pagano; Vinicius Farias Campos; Kauê Rodrigues Martins; Rodrigo Casquero Cunha (Brazilian Journal of Microbiology, 2025)

Analysis of the ecotoxicity of waste generated in a laundry in the textile center of the Agreste region of Pernambuco using zebrafish (Danio rerio) as a bioindicator - Paula Raíza Alves Cavalcante; Jadson Freitas da Silva; Renatta Priscila Ferreira Silva; Matheus Victor Viana de Melo; Maria Letícia Santos Carnaúba da Silva; Maria Eduarda Borges de Almeida; Samara da Silva Gomes; Yuri Mateus Lima de Albuquerque; Rodrigo Cândido Passos da Silva; Pabyton Gonçalves Cadena; Rosângela Gomes Tavares (Environmental Science and Pollution Research, 2025)

Private ownership of water and wastewater systems: Assessing health impacts - Rodrigo França Chaves; Adriano Borges Costa (Utilities Policy, 2025)

Static and dynamic controlled atmosphere storage and 1-methylcyclopropene treatment of ‘Cripps Pink’ apples: Linking sensory perception, volatile compounds, and quality - Fernanda de Candido de Oliveira; Manoela Meira Balzan; Barbara Cecconi Deon; Madison Willy Cordeiro; Carine Borges Batista; Francis Júnior Soldateli; Lucas Mallmann Wendt; Fabio Rodrigo Thewes; Vanderlei Both; Auri Brackmann; Daniel Alexandre Neuwald; Roger Wagner (Food Research International, 2025)

Clinical and pathological characterization of a feline intestinal large granular lymphocyte lymphoma (LGLL) - Camila Issa Amaral; Lorena Santos Bezerra; Acácia Eduarda de Jesus Nascimento; Nayara Toledo da Silva; Lize Amanda Basaglia Borges; Paloma Helena Sanches da Silva; Letícia Monteiro Barbosa; Anelise Carvalho Nepomuceno; Rodrigo dos Santos Horta; Geovanni Dantas Cassali; Ayisa Rodrigues Oliveira (Veterinary Research Communications, 2025)

Reproductive biology of Eremanthus incanus (Less.) Less., an endemic exploited Asteraceae from Brazil - Luiz Filipe Maravilha; João Paulo Raimundo Borges; Elisa Jorge de Morais; Evandro Luiz Mendonça Machado; Leonardo Ré Jorge; André Rodrigo Rech; Miranda Titon (Trees, 2025)

Impact of dietary supplementation with Synechococcus elongatus PCC 7942 expressing a β-glucosidase from Amazonian soil on the physiology of zebrafish (Danio rerio) fed a soybean meal-rich diet - Andrea Idelette Hernandez; Raíza dos Santos Azevedo; Mirna Enríquez Reyes; Beatriz Xavier Figueiredo; Isaac dos Santos Flores; Luri Salim Abou Anni; Tony Silveira; Marcelo Borges Tesser; Rodrigo Desessards Jardim; Antônio Sérgio Varella Junior; Bruna Felix Nornberg; Luis Fernando Marins (Journal of Applied Phycology, 2025)

Quality of ‘Cripps Pink’ Apples Stored in Controlled Atmosphere with Complementary Techniques - Carine Borges Batista; Vanderlei Both; Francis Júnior Soldateli; Lucas Mallmann Wendt; Vagner Ludwig; Auri Brackmann; Giovani Gonçalves dos Santos; Flavio Roberto Thewes; Fabio Rodrigo Thewes (Applied Fruit Science, 2025)

A validated ultra-performance liquid chromatography with tandem mass spectrometry method for the quantification of Brazilian green propolis main compounds - Mário Ferreira Conceição Santos; Giulia Stavrakas Mirada; Joice Olinda do Couto; Gilvana de Oliveira Costa; Ana Carla Rangel Rosa; Carly Henrique Gambeta Borges; Eduardo José Crevelin; Luciana Silva de Araújo; Jairo K. Bastos; Rodrigo C. S. Veneziani; Sérgio R. Ambrósio (Natural Product Research, 2025)

Postharvest 1-Butanol Treatment to ‘Midori’ Cabbage as a Regulator of Pigments Degradation, Color Changes and Overall Quality After Storage at Different Temperatures - Mateus Gaiardo dos Santos; Lilian Osmari Uhlmann; Bruna Regina Carvalho Pinto; Guilherme Zanon Peripolli; Luise Victoria Agnes; Carine Borges Batista; Kaliandra Zottele Nunes; Roger Wagner; Vanderlei Both; Fabio Rodrigo Thewes (Journal of Plant Growth Regulation, 2025)

Interaction of nitric oxide and extremely low oxygen storage on volatile organic compounds and overall quality of ‘Maxi Gala’ apples - Francis Júnior Soldateli; Carine Borges Batista; Bruna Regina Carvalho Pinto; Lucas Mallmann Wendt; Barbara Cecconi Deon; Vagner Ludwig; Fabio Rodrigo Thewes; Cristiano André Steffens; Auri Brackmann; Vanderlei Both (Postharvest Biology and Technology, 2025)

Geotechnical centrifuge modelling of thermal improvement processes in clayey soils for offshore anchoring purposes - Marina de Souza Ferreira; Fernando Saboya; Sérgio Tibana; Rodrigo Martins Reis; John Scott McCartney; Ricardo Garske Borges (Ocean Engineering, 2025)

Challenges in achieving partial nitrification: Simultaneous nitrification-denitrification as the dominant pathway in municipal wastewater treatment - Paula Yumi Takeda; Carolina Tavares Paula; Rodrigo Braz Carneiro; André do Vale Borges; Luana Cardoso Grangeiro; Márcia Helena Rissato Zamariolli Damianovic (Journal of Environmental Chemical Engineering, 2025)

Primary intracranial squamous cell carcinoma in a mule - João R.C. Brito Junior; Yanca G.S. Soares; Laynaslan A. Soares; Ismael L. Borges; Rodrigo C. Alves; Daniel M. Assis; Glaucia D. Kommers; Antonio F.M. Dantas; Glauco J.N. Galiza (Journal of Comparative Pathology, 2025)

The mitochondriotropic antioxidants AntiOxBEN2 and AntiOxCIN4 are structurally-similar but differentially alter energy homeostasis in human skin fibroblasts - José Teixeira; Sofia Benfeito; Rodrigo Carreira; André Barbosa; Ricardo Amorim; Ludgero C. Tavares; John G. Jones; Nuno Raimundo; Fernando Cagide; Catarina Oliveira; Fernanda Borges; Werner J.H. Koopman; et al. (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2025)

Comparative economic, energy, and environmental analysis of fuel cell and electric eVTOL systems: Case study of Iberian Peninsula - Néstor Velaz-Acera; Rodrigo Ruiz-Marín; David Borge-Diez (Journal of Cleaner Production, 2025)

Taxonomic identity, but not evolutionary relatedness, determines the carbon stock and uptake of tropical forests trees - Alisson Borges Miranda Santos; Cléber Rodrigo de Souza; Fernanda Coelho de Souza; Natália de Aguiar-Campos; Vinicius Andrade Maia; Nathalle Cristine Alencar Fagundes; Aurélio de Jesus Rodrigues Pais; Gabriela Gomes Pires; Mariana Caroline Moreira Morelli; Jean Daniel Morel; Rubens Manoel dos Santos (Acta Oecologica, 2025)

What fire didn’t take away: plant growth-promoting microorganisms in burned soils of old-growth Nothofagus forests in Los Andes Cordillera - Leonardo Almonacid-Muñoz; Héctor Herrera; Andrés Fuentes-Ramírez; Rodrigo Vargas-Gaete; Octavio Toy-Opazo; Paulo Henrique de Oliveira Costa; Rafael Borges da Silva Valadares (Plant and Soil, 2025)

Ethylene Management Affects the Bunches Quality of ‘BRS Isis’ Table Grapes After Storage - Francis Júnior Soldateli; Vanderlei Both; Carine Borges Batista; Magno Roberto Pasquetti Berghetti; Vagner Ludwig; Lucas Mallmann Wendt; Auri Brackmann; Fabio Rodrigo Thewes (Applied Fruit Science, 2025)

Regional relationship between total alkalinity and salinity in the surface waters of the western South Atlantic margin - Cíntia Albuquerque; Gizyelle Miguel; Cássia de Oliveira Farias; Luana Pinho; Humberto Marotta; Iole Beatriz Marques Orselli; Mariah de Carvalho-Borges; Edmo Campos; Rodrigo Kerr; Leticia Cotrim da Cunha (Regional Studies in Marine Science, 2025)

Stability of milk proteins subjected to UHT treatments: challenges and future perspectives - Alisson Borges de Souza; Rodrigo Stephani; Guilherme M. Tavares (Critical Reviews in Food Science and Nutrition, 2024)

Investigating the significance of the transgenerational impact of high and repeated doses of ivermectin: Effects on paternal testis histopathology, pups' development, and sexual behavior - Natalia Moreira; Kassia de Carvalho; Gabriel Aur Borges; Lais Coelho Cortez; Laura de Macedo Amado; Rodrigo Augusto Foganholi da Silva; Flora Cordeiro; Maria Martha Bernardi (Reproductive Toxicology, 2024)

Use of infrared and mass spectrometry for the discrimination of metabolites from different stages of Schinus terebinthifolia Raddi leaves - Rodrigo Borges de Araujo Gomes; Fabiana Gomes Ruas; José Aires Ventura; Paulo Roberto Filgueiras; Ricardo Machado Kuster (Biochemical Systematics and Ecology, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Total replacing soybean meal with extruded urea in supplements on the intake, ruminal, and metabolic parameters of beef cattle during the rainy and wet-dry transition seasons - Gabriella Jorgetti de Moraes; Luís Carlos Vinhas Ítavo; Camila Celeste Brandão Ferreira Ítavo; Alexandre Menezes Dias; Gelson dos Santos Difante; Vanessa Zirondi Longhini; Rodrigo da Costa Gomes; Antonio Leandro Chaves Gurgel; Marcus Vinicius Garcia Niwa; Noemila Débora Kozerski; Marlova Cristina Mioto da Costa; Adriélli Dias Borges; et al. (Tropical Animal Health and Production, 2024)

Sporocysts of Sarcocystis bertrami (syn. Sarcocystis fayeri) shed by dogs: Molecular analysis, morphometry and pattern of excretion - Caroline Dantas Primo Marques; Bruno Wilians Souza da Silva; Yuri Vinícius Silva Nogueira; Taynar Lima Bezerra; Waléria Borges-Silva; Rodrigo Martins Soares; Luís Fernando Pita Gondim (Veterinary Parasitology, 2024)

The mlpt smORF gene is essential for digestive physiology and molting during nymphal stages in the kissing bug Rhodnius prolixus - Carina Azevedo Oliveira Silva; Sandy da Silveira Alves; Bruno da Costa Rodrigues; Jonatha Anderson Fraga Egidio; Lupis Ribeiro; Carlos Logullo; Flavia Borges Mury; Daniele das Graças Santos; Taynan Portal; Cintia Monteiro-de-Barros; José Roberto da Silva; José Luciano Nepomuceno-Silva; et al. (Insect Biochemistry and Molecular Biology, 2024)

Water restriction alters seed bank traits and ecology in Atlantic Forest seasonal forests under climate change - Patrícia Borges Dias; Sustanis Horn Kunz; José Eduardo Macedo Pezzopane; Talita Miranda Teixeira Xavier; João Paulo Fernandes Zorzanelli; João Vitor Toledo; Lhoraynne Pereira Gomes; Rodrigo Gomes Gorsani (Global Change Biology, 2024)
The soil seed bank (SSB) is one of the key mechanisms that ensure the perpetuity of forests, but how will it behave in the scenarios projected for the future climate? Faced with this main question, still little explored in seasonal tropical forests, this study evaluated the germination, ecological attributes, and functional traits of the SSB in a seasonal forest in the Atlantic Forest. Forty‐eight composite samples of the SSB were collected from 12 plots, distributed across four treatments, each with 12 replicates. The samples were placed in two climate‐controlled greenhouses, establishing two environments of controlled climatic conditions, both with two levels of water, as follows: Cur: current scenario without water restriction; Cur_WR: current scenario with water restriction; RCP8.5: future scenario without water restriction; RCP8.5_WR: future scenario with water restriction. The germinants were identified, and their ecological attributes and functional traits were obtained. Leaf area and biomass production, differences in abundance, richness, and diversity were evaluated, along with analysis of variance to assess the interaction between water levels and scenarios. All ecological attributes and functional traits evaluated drastically decreased in the future projection with water restriction, with this restriction being the main component influencing this response. The increased temperature in the future scenario significantly raised water consumption compared to the current scenario. However, persistent water restrictions in the future could undermine the resilience of seasonal forests, hindering seed germination in the soil. Richness and abundance were also adversely affected by water scarcity in the future scenario, revealing a low tolerance to the projected prolonged drought. These changes found in the results could alter the overall structure of seasonal forests in the future, as well as result in the loss of the regeneration potential of the SSB due to decreased seed viability and increased seedling mortality.

Unveiling the reproduction of Proteopsis argentea (Asteraceae): how the complex pollination system might influence its conservation status - João Paulo Raimundo Borges; Ilmara Aparecida Oliveira Ferreira; Danubia Natalina Silva; Cinthia Soares Novaes; Ana Carolina Pereira Machado; Gudryan Jackson Baronio; Leonardo Ré Jorge; André Rodrigo Rech (Brazilian Journal of Botany, 2024)

Phytochemical composition of aerial parts and roots of Pfaffia glomerata (Spreng.) Pedersen and anticholinesterase, antioxidant, and antiglycation activities - Rodrigo Rodrigues Franco; Rafaella Martins Franco; Allisson Benatti Justino; Ana Luiza Silva Borges; Vinícius Prado Bittar; Natieli Saito; André Lopes Saraiva; Nilson Nicolau Júnior; Wagner Campos Otoni; Foued Salmen Espindola (Protoplasma, 2024)

Effects of Myrcia pubipetala Miq (Myrtaceae) extract on innate inflammatory response - Pâmela Pacassa Borges; Larissa Benvenutti; Aline Lana Schneider; Marcelo Rodrigo Franke Echterhoff; Bruna Gonçalves Lopes; Diogo Alexandre Siebert; Gustavo Amadeu Micke; Luciano Vitali; Michele Debiasi Alberton; Nara Lins Meira Quintão; José Roberto Santin; Isabel Daufenback Machado (Natural Product Research, 2024)

Are native microalgae consortia able to remove microplastics from wastewater effluents? - Valdemira Afonso; Rodrigo Borges; Brígida Rodrigues; Raúl Barros; Maria João Bebianno; Sara Raposo (Environmental Pollution, 2024)

Organosulfur and Organoselenium Functionalized Benzimidazo[1,2-a]quinolines: From Experimental and Theoretical Photophysics to All-Solution-Processed OLEDs - Rodrigo Borges da Silva; Felipe Lange Coelho; Henrique de Castro Silva Junior; José Carlos Germino; Teresa Dib Zambon Atvars; Fabiano Severo Rodembusch; Luís Gustavo Teixeira Alves Duarte; Paulo Henrique Schneider (Journal of Fluorescence, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Absence of adverse effects of Blutaparon portulacoides (A.St.-Hil.) Mears in mice exposed during pregnancy - Silvia Cordeiro das Neves; Renata Coelho Rodrigues Noronha; Antonio Carlos Duenhas Monreal; Luís Adriano Santos do Nascimento; Adauto Lima Cardoso; Flávia dos Santos Tavares; Bethânia Borges Tura; Roberto da Silva Gomes; Candida Aparecida Leite Kassuya; Viktor Krejci Nunes; Marcos José Salvador; Rodrigo Juliano Oliveira (South African Journal of Botany, 2024)

Dynamic controlled atmosphere monitored by respiratory quotient as a new method to store pears: Effect on the volatile compounds profile and general quality - Lucas Mallmann Wendt; Vagner Ludwig; Fabio Rodrigo Thewes; Francis Júnior Soldateli; Carine Borges Batista; Flavio Roberto Thewes; Caio Mizuto Fukui; Auri Brackmann; Vanderlei Both; Jose Masanori Katsurayama (Postharvest Biology and Technology, 2024)

Prior denaturation and aggregation of whey proteins: is this a useful strategy for increasing the content of these proteins in UHT high-protein dairy beverages? - Alisson Borges de Souza; Ana Augusta Odorissi Xavier; Rodrigo Stephani; Guilherme M. Tavares (Food and Bioproducts Processing, 2024)

Exploring the potential of tannin-rich tree bark extracts in combating foodborne diseases and gastric cancer - João Gilberto Meza Ucella-Filho; Mario Sérgio Lorenço; Bruna Rafaella Ferreira da Silva; Vanuzia Rodrigues Fernandes Ferreira; Jessica Raquel Borges Monteiro; Nicolly Soares Ferreira; Maria das Graças Cardoso; Rodrigo Rezende Kitagawa; Juliana Alves Resende; Ananias Francisco Dias Junior; Roberta Hilsdorf Piccoli; Fábio Akira Mori (Food Bioscience, 2024)

Magnetic heterostructures of NiFe2O4 and TiO2: Pechini synthesis, characterization and photocatalytic performance in arsenite oxidation - Giulia Caroline de Cristo Borges; Isadora Roberta Verdi; Michel Zampieri Fidelis; Henrique Emilio Zorel Junior; Giane Gonçalves Lenzi; Éder Carlos Ferreira de Souza; Odivaldo Cambraia Alves; Rodrigo Brackmann (Journal of Water Process Engineering, 2023)

Lipidomic analysis identified potential predictive biomarkers of statin response in subjects with Familial hypercholesterolemia - Alvaro Cerda; Raul Hernandes Bortolin; Marcos Yukio Yoshinaga; Renata Caroline Costa de Freitas; Carolina Dagli-Hernandez; Jessica Bassani Borges; Victor Fernandes de Oliveira; Rodrigo Marques Gonçalves; Andre Arpad Faludi; Gisele Medeiros Bastos; Rosario Dominguez Crespo Hirata; Mario Hiroyuki Hirata (Chemistry and Physics of Lipids, 2023)

LDLR and PCSK9 3´UTR variants and their putative effects on microRNA molecular interactions in familial hypercholesterolemia: a computational approach - Renata Caroline Costa de Freitas; Raul Hernandes Bortolin; Jessica Bassani Borges; Victor Fernandes de Oliveira; Carolina Dagli-Hernandez; Elisangela da Silva Rodrigues Marçal; Gisele Medeiros Bastos; Rodrigo Marques Gonçalves; Andre Arpad Faludi; Vivian Nogueira Silbiger; André Ducati Luchessi; Rosario Dominguez Crespo Hirata; et al. (Molecular Biology Reports, 2023)

Plants of the Serra do Mucambo: a checklist of a remnant of deciduous seasonal forest within the Caatinga domain in Bahia, Brazil - Denis Nunes Carvalho; Ilana Cunha de Oliveira; Grênivel Mota da Costa; Rodrigo Lopes Borges; Andreza Oliveira Matos; Aline Matos Souza; Milena Evangelista-dos-Santos; Matteus Freitas de Oliveira; Reyjane Patricia de Oliveira (Brazilian Journal of Botany, 2023)

Physical and chemical characteristics of Schinus terebinthifolia Raddi (Brazilian peppertree) fruits at different stages of maturation - Nataly Senna Gerhardt Barraqui; José Aires Ventura; Fabiana Gomes Ruas; Rodrigo Borges de Araujo Gomes; Betina Pires Oliveira Lovatti; Samantha Ribeiro Campos da Silva; Paulo Roberto Filgueiras; Ricardo Machado Kuster (Biochemical Systematics and Ecology, 2023)

Tropical headwater streams and the role of non-native species on fish assemblage’s diversity - Bruno R. B. Santos; Fabrício B. Teresa; Pedro P. Borges; Lilian Casatti; Francisco L. Tejerina-Garro; Paulo S. Pompeu; Evanilde Benedito; Fernando R. Carvalho; Mauricio Cetra; Murilo S. Dias; Yzel R. Súarez; Thiago Santos; et al. (Biological Invasions, 2023)

Spatiotemporal variability of dissolved inorganic macronutrients along the northern Antarctic Peninsula (1996–2019) - Thiago Monteiro; Sian F. Henley; Ricardo César Gonçalves Pollery; Carlos Rafael Borges Mendes; Mauricio Mata; Virginia Maria Tavano; Carlos Alberto Eiras Garcia; Rodrigo Kerr (Limnology and Oceanography, 2023)
The northern Antarctic Peninsula is a key region of the Southern Ocean due to its complex ocean dynamics, distinct water mass sources, and the climate‐driven changes taking place in the region. Despite the importance of macronutrients in supporting strong biological carbon uptake and storage, little is known about their spatiotemporal variability along the northern Antarctic Peninsula. Hence, we explored for the first time a 24‐year time series (1996–2019) in this region to understand the processes involved in the spatial and interannual variability of macronutrients. We found high macronutrient concentrations, even in surface waters and during strong phytoplankton blooms. Minimum concentrations of dissolved inorganic nitrogen (DIN; 16 μ mol kg −1 ), phosphate (0.7 μ mol kg −1 ), and silicic acid (40 μ mol kg −1 ) in surface waters are higher than those recorded in surrounding regions. The main source of macronutrients is the intrusions of Circumpolar Deep Water and its modified variety, while local sources (organic matter remineralization, water mass mixing, and mesoscale structures) can enhance their spatiotemporal variability. However, we identified a depletion in silicic acid due to the influence of Dense Shelf Water from the Weddell Sea. Macronutrient concentrations show substantial interannual variability driven by the balance between the intrusions of modified Circumpolar Deep Water and advection of Dense Shelf Water, which is largely modulated by the Southern Annular Mode (SAM) and to some extent by El Niño‐Southern Oscillation (ENSO). These findings are critical to improving our understanding of the natural variability of this Southern Ocean ecosystem and how it is responding to climate changes.

Characterization and subchronic oral toxicity of Pentaclethra macroloba (pracaxi) oil in Rattus norvegicus (lin. Wistar) - Bruna de Souza Eberhart; Claudia Marie Komiyama; Maria Fernanda de Castro Burbarelli; Vivian Aparecida Rios Castilho Heiss; Rodrigo Garófallo Garcia; Rafael Borges; Gisele Aparecida Felix; Claudia Andrea Lima Cardoso; Paulo Henrique Braz; Cássia Regina Teodoro; Felipe Cardoso Serpa; Erika Rosendo de Sena Gandra (Toxicon, 2023)

New near-mine prospecting approach using multivariate analysis and reflectance spectroscopy to define surface footprint: A case study of the Pequizão Gold Deposit, Crixás Greenstone Belt, Central Brazil - Anderson Matias dos Santos; Adalene Moreira Silva; Catarina Lauboré Bemfica Toledo; Rodrigo dos Reis Salles; Diego Fernando Ducart; Luana Machado Campos; Caio Cesar Aguiar Borges; Marcelo Pereira Campos; Bruno Araújo dos Santos (Journal of Geochemical Exploration, 2023)

Failure to predict amikacin elimination in critically ill patients with cancer based on the estimated glomerular filtration rate: applying PBPK approach in a therapeutic drug monitoring study - João Paulo Telles; Mariana Suelotto Diegues; Karen Cristina Migotto; Olivia de Souza Borges; Rodrigo Reghini; Brenda Vianna Gavazza; Leonardo Pinto; Pedro Caruso; Ivan Leonardo França e Silva; Stephan Schmidt; Fernanda de Lima Moreira (European Journal of Clinical Pharmacology, 2023)

Rhomb-I, a P–I metalloproteinase from Lachesis muta rhombeata venom degrades vessel extra cellular matrix components and impairs platelet aggregation - Valéria Gonçalves de Alvarenga; Luciana S. Oliveira; Gustavo O. Santos; Dan E. Vivas-Ruiz; Márcia Helena Borges; Rodrigo C.G. de Souza; Johannes A. Eble; Ana Maria Moura-da-Silva; Eladio F. Sanchez (Toxicon, 2023)

Spatial distance explains the periphyton metacommunity structure of a neotropical stream network - Pedro Henrique Francisco Oliveira; Karine Borges Machado; Fabrício Barreto Teresa; Rodrigo Assis de Carvalho; Manuel Eduardo Ferreira; Francisco Leonardo Tejerina-Garro; Priscilla Carvalho; Carla Ferragut; Adriano Sanches Melo; João Carlos Nabout (Hydrobiologia, 2023)

Cryptophytes: An emerging algal group in the rapidly changing Antarctic Peninsula marine environments - Carlos Rafael Borges Mendes; Raul Rodrigo Costa; Afonso Ferreira; Bruno Jesus; Virginia Maria Tavano; Tiago Segabinazzi Dotto; Miguel Costa Leal; Rodrigo Kerr; Carolina Antuarte Islabão; Andréa de Oliveira da Rocha Franco; Mauricio M. Mata; Carlos Alberto Eiras Garcia; et al. (Global Change Biology, 2023)
The western Antarctic Peninsula (WAP) is a climatically sensitive region where foundational changes at the basis of the food web have been recorded; cryptophytes are gradually outgrowing diatoms together with a decreased size spectrum of the phytoplankton community. Based on a 11‐year (2008–2018) in‐situ dataset, we demonstrate a strong coupling between biomass accumulation of cryptophytes, summer upper ocean stability, and the mixed layer depth. Our results shed light on the environmental conditions favoring the cryptophyte success in coastal regions of the WAP, especially during situations of shallower mixed layers associated with lower diatom biomass, which evidences a clear competition or niche segregation between diatoms and cryptophytes. We also unravel the cryptophyte photo‐physiological niche by exploring its capacity to thrive under high light stress normally found in confined stratified upper layers. Such conditions are becoming more frequent in the Antarctic coastal waters and will likely have significant future implications at various levels of the marine food web. The competitive advantage of cryptophytes in environments with significant light level fluctuations was supported by laboratory experiments that revealed a high flexibility of cryptophytes to grow in different light conditions driven by a fast photo‐regulating response. All tested physiological parameters support the hypothesis that cryptophytes are highly flexible regarding their growing light conditions and extremely efficient in rapidly photo‐regulating changes to environmental light levels. This plasticity would give them a competitive advantage in exploiting an ecological niche where light levels fluctuate quickly. These findings provide new insights on niche separation between diatoms and cryptophytes, which is vital for a thorough understanding of the WAP marine ecosystem.

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Antarctica Slope Front bifurcation eddy: A stationary feature influencing CO2 dynamics in the northern Antarctic Peninsula - Brendon Yuri Damini; Raul Rodrigo Costa; Tiago S. Dotto; Carlos Rafael Borges Mendes; Juan Camilo Torres-Lasso; Marina do V.C. Azaneu; Mauricio M. Mata; Rodrigo Kerr (Progress in Oceanography, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Canine distemper virus and canine adenovirus type 1 co-infection in a free-living hoary fox (Lycalopex vetulus) from Brazil - Maraya Lincoln Silva; Mayara Grego Caiaffa; André Luiz Mota da Costa; Rodrigo Hidalgo Friciello Teixeira; Ticiana Brasil Ervedosa; Eduardo Ferreira Machado; Pedro Enrique Navas Suárez; Rodrigo Albergaria Réssio; Cinthya Cirqueira Borges; Isis Paixão de Jesus; Julia de Carvalho; Ketlyn Bolsachini Figueiredo; et al. (Brazilian Journal of Microbiology, 2023)

Sedimentation in UHT high-protein dairy beverages: Influence of sequential preheating coupled with homogenisation or supplementation with carbohydrates - Alisson Borges de Souza; Ana Augusta O. Xavier; Rodrigo Stephani; Guilherme M. Tavares (International Dairy Journal, 2023)

Heat stress negatively affects physiology and morphology during germination of Ormosia coarctata (Fabaceae, Papilionoideae) - Luciane Pereira Reis; Eduardo Euclydes de Lima e Borges; Rodrigo Cupertino Bernardes; Genaina Aparecida de Souza; Renan dos Santos Araújo (Protoplasma, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Effects of different probiotic strains B. lactis, L. rhamnosus and L. reuteri on brain-intestinal axis immunomodulation in an endotoxin-induced inflammation - Monique Michels; Gabriel Fernandes Alves Jesus; Mariane Rocha Abatti; Emily Córneo; Luana Cucker; Heloisa de Medeiros Borges; Natan da Silva Matos; Luana Bezerra Rocha; Rodrigo Dias; Carla Sasso Simon; Ana Paula Lorenzen Voytena; Marina Rossetto; et al. (Molecular Neurobiology, 2022)

A sustainable approach in the management of Callosobruchus maculatus: essential oil of Protium heptaphyllum and its major compound d-limonene as biopesticides - Rosalba Maria Borges de Andrade Rodrigues; Lucia da Silva Fontes; Rodrigo de Carvalho Brito; Douglas Rafael e Silva Barbosa; Antonia Maria das Graças Lopes Citó; Iolanda Souza do Carmo; Emanoela Maria de Jesus Sousa; Gutierres Nelson Silva (Journal of Plant Diseases and Protection, 2022)

SIA‐BRA: A database of animal stable carbon and nitrogen isotope ratios of Brazil - Thaís Rovere Diniz‐Reis; Fernanda Gaudio Augusto; Adibe Luiz Abdalla Filho; Maria Gabriella da Silva Araújo; Siglea Sanna Freitas Chaves; Rodrigo Figueiredo Almeida; Elen Blanco Perez; Carla da Penha Simon; Janaína Leite de Souza; Cristiane Formigosa Gadelha da Costa; Taciana Figueiredo Gomes; Melissa Gaste Martinez; et al. (Global Ecology and Biogeography, 2022)
Motivation SIA‐BRA is a data set that compiles stable carbon (C) and nitrogen (N) isotope ratios of terrestrial and aquatic animals sampled in Brazilian biomes and coastal marine areas. Stable isotope ratios are helpful in animal ecology for several reasons; for instance, they can be used to investigate trophic niches, energy sources (diet tracing) and to track migration patterns. The Neotropics are considered one of the most undersampled regions of the world. Given that Brazil is a continental country where most of the dietary ecology of animal species is under‐assessed, we believe that the SIA‐BRA can provide important complementary information to address this gap in the literature. Additionally, the SIA‐BRA data set allows future investigations to address many questions concerning diet tracing, habitat use, food webs, foraging ecology, physiological aspects and effects of phylogeny on dietary ecology. Main type of variable investigated Carbon and nitrogen stable isotope ratios for terrestrial and aquatic animals. Spatial location and grain The SIA‐BRA included animal tissues sampled in 964 sites in the main Brazilian biomes and coastal marine areas. Time period The data represent information published and/or sampled from 1984 to 2021. Major taxa studied and measurement level The SIA‐BRA contains isotopic data of c . 21,804 non‐captive wildlife specimens, excluding livestock production or laboratory experiments. They were 13,881 vertebrates and 7,923 invertebrates. They were divided into the following habitats: terrestrial (30% of the total), freshwater (27%), oceanic (40%) and estuarine (4%). There were 11 phyla, with a clear dominance of Chordata (64%) and Arthropoda (29%), 36 classes, 154 orders, 473 families, 894 genera and 1,157 species. Software format Data are supplied as a comma‐delimited text file (.csv).

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Large-scale Degradation of the Tocantins-Araguaia River Basin - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Alberto Akama; José Dilermando Andrade Filho; Valter M. Azevedo-Santos; Marcus Vinicius Moreira Barbosa; Luis Mauricio Bini; Marcelo Fulgêncio Guedes Brito; Carlos Roberto dos Anjos Candeiro; Érica Pellegrini Caramaschi; Priscilla Carvalho; Rodrigo Assis de Carvalho; et al. (Environmental Management, 2021)

Heat stress-mediated effects on the morphophysiological, biochemical, and ultrastructural parameters of germinating Melanoxylon brauna Schott. seeds - Luciane Pereira Reis; Eduardo Euclydes de Lima e Borges; Danielle S. Brito; Rodrigo Cupertino Bernardes; Renan dos Santos Araújo (Plant Cell Reports, 2021)

Effect of Amoxicillin on Nitrogen Oxidation Bacteria Present in Activated Sludge: Respirometry Investigation - Júlia Kersul Faria; Ana Carolina Santana Conceição; Márcio Yukihiro Kohatsu; Alessandra Borges Okamoto; Lúcia Helena Coelho; Eduardo Lucas Subtil; Rodrigo de Freitas Bueno (Current Microbiology, 2021)

Statistical methods for more precise selection of biofortified common bean lines - Nerinéia Dalfollo Ribeiro; Greice Rosana Kläsener; Rodrigo de Morais Borges (Euphytica, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Dynamics of an intense diatom bloom in the Northern Antarctic Peninsula, February 2016 - Raul Rodrigo Costa; Carlos Rafael Borges Mendes; Virginia Maria Tavano; Tiago Segabinazzi Dotto; Rodrigo Kerr; Thiago Monteiro; Clarisse Odebrecht; Eduardo Resende Secchi (Limnology and Oceanography, 2020)
Diatoms are considered the main base of the Southern Ocean food web as they are responsible for more than 85% of its annual primary production and play a crucial role in the Antarctic trophic structure and in the biogeochemical cycles. Within this context, an intense diatom bloom reaching > 45 mg m −3 of chlorophyll a was registered in the Northern Antarctic Peninsula (NAP) during a late summer study in February 2016. Given that nutrient concentrations and grazing activities were not identified here as limiting factors on the bloom development, the aim of this study was to evaluate the effect of water column structure (stability and upper mixed layer depth) on the phytoplankton biomass and composition in the NAP. The diatom bloom, mainly composed by the large centric Odontella weissflogii (mostly > 70 μ m in length), was associated with a local ocean carbon dioxide uptake that reached values greater than −60 mmol m −2 d −1 . We hypothesize that the presence of a vertically large water column stability barrier, just below the pycnocline, was the main driver allowing for the development of the intense diatom bloom, particularly in the Gerlache Strait. Contrarily, a shift from diatoms to dinoflagellates (mainly Gymnodiniales μ m) was observed associated with conditions of a highly stable thin layer. The results suggest that a large fraction of this intense diatom bloom is in fast sinking process, associated with low grazing pressure, showing a crucial role of diatoms for the efficiency of the biological carbon pump in this region.

Photocatalytic Properties of Commercially Available TiO2: Study of Fotosan® and InterBrasil® FA-101 for H2S Degradation Using UV and Solar Radiation - Eduardo Borges Lied; Camilo Freddy Mendoza Morejon; Rodrigo Leonardo de Oliveira Basso; Ana Paula Trevisan; Fernanda de Oliveira Tavares; Marcela Boroski; Jacqueline Ferandin Honório (Water, Air, & Soil Pollution, 2020)

Selection strategies for increasing the yield of high nutritional value leaf mass in Urochloa hybrids - Beatriz Tomé Gouveia; Sanzio Carvalho Lima Barrios; Cacilda Borges do Valle; Rodrigo da Costa Gomes; Wyverson Kim Rocha Machado; Júlio Sílvio de Sousa Bueno Filho; José Airton Rodrigues Nunes (Euphytica, 2020)

Temporal shifts on tree species niches: how do they affect species dynamics and community diversity? - Vinícius Andrade Maia; Natalia de Aguiar-Campos; Cléber Rodrigo de Souza; Nathalle Cristine Alencar Fagundes; Alisson Borges Miranda Santos; Aurélio de Jesus Rodrigues Pais; Jean Daniel Morel; Camila Laís Farrapo; Rubens Manoel dos Santos (Plant Ecology, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Interaction with Pantoea agglomerans Modulates Growth and Melanization of Sporothrix brasiliensis and Sporothrix schenckii - Rodrigo Almeida-Paes; Fábio Brito-Santos; Manoel Marques Evangelista Oliveira; Alexandre Melo Bailão; Clayton Luiz Borges; Glauber Ribeiro de Souza Araújo; Susana Frases; Célia Maria de Almeida Soares; Rosely Maria Zancopé-Oliveira (Mycopathologia, 2019)

Changes in the feeding ecology of South American sea lions on the southern Brazilian coast over the last two decades of excessive fishing exploration - Rodrigo Machado; Larissa Rosa de Oliveira; Paulo Henrique Ott; Pablo Denuncio; Manuel Haimovici; Luis Gustavo Cardoso; Daniel Danilewicz; Ignacio Benites Moreno; Márcio Borges-Martins (Hydrobiologia, 2018)

Anti-inflammatory and antialgic actions of a nanoemulsion of Rosmarinus officinalis L. essential oil and a molecular docking study of its major chemical constituents - Raphaelle Sousa Borges; Emerson Silva Lima; Hady Keita; Irlon Maciel Ferreira; Caio Pinho Fernandes; Rodrigo Alves Soares Cruz; Jonatas Lobato Duarte; Josué Velázquez-Moyado; Brenda Lorena Sánchez Ortiz; Andrés Navarrete Castro; Jaderson Vieira Ferreira; Lorane Izabel da Silva Hage-Melim; et al. (Inflammopharmacology, 2018)

Evaluation of antibacterial activity of the bark and leaf extracts of Brosimum gaudichaudii Trécul against multidrug resistant strains - Joelma da Costa Borges; Michele Cezimbra Perim; Rodrigo Orlandini de Castro; Thiago Antônio de Sousa Araújo; Tadeu José da Silva Peixoto Sobrinho; Ana Carolina Oliveira da Silva; Sandra Maria Botelho Mariano; Solange Cristina Carreiro; Maria Cristina da Silva Pranchevicius (Natural Product Research, 2017)

Inferring tropical popcorn gene pools based on molecular and phenotypic data - Gabriel Borges Mundim; José Marcelo Soriano Viana; Ciro Maia; Geísa Pinheiro Paes; Rodrigo Oliveira DeLima; Mágno Sávio Ferreira Valente (Euphytica, 2015)

Hydrosedimentology of nested subtropical watersheds with native and eucalyptus forests - Miriam Fernanda Rodrigues; José Miguel Reichert; Jean Paolo Gomes Minella; Leandro Dalbianco; Rodrigo Luiz Ludwig; Rafael Ramon; Lilian Alessandra Rodrigues; Norton Borges Júnior (Journal of Soils and Sediments, 2014)

The pollen of Caesalpinia pyramidalis Tul. is toxic to honeybees (Apis mellifera) - Igor Ricardo Batista Vieira de Melo; Mateus Cardoso da Costa Lages; Diego Passos dos Santos; Patrício Borges Maracajá; Rodrigo Alboim de Paiva Fernandes Rodrigues; Benito Soto-Blanco (Arthropod-Plant Interactions, 2013)

Genetic diversity and path analysis for nitrogen use efficiency in popcorn inbred lines - Gabriel Borges Mundim; José Marcelo Soriano Viana; Ciro Maia; Geísa Pinheiro Paes; Rodrigo Oliveira DeLima (Euphytica, 2013)

Relative efficiency of the genotypic value and combining ability effects on reciprocal recurrent selection - José Marcelo Soriano Viana; Rodrigo Oliveira DeLima; Gabriel Borges Mundim; Aurinelza Batista Teixeira Condé; Aloisio Alcantara Vilarinho (Theoretical and Applied Genetics, 2013)

Prevalence of and risk factors for bovine respiratory syncytial virus (BRSV) infection in non-vaccinated dairy and dual-purpose cattle herds in Ecuador - Luis Rodrigo Saa; Anselmo Perea; Diego Vinicio Jara; Antonio José Arenas; Ignacio Garcia-Bocanegra; Carmen Borge; Alfonso Carbonero (Tropical Animal Health and Production, 2012)

Population of Scaptocoris castanea Perty (Hemiptera: Cydnidae) in a Crop–Livestock Integration System - Marcelo Francisco Arantes Pereira; R M Peres; Rodrigo dos Santos Borges (Neotropical Entomology, 2012)

Synchronous Oral Paracoccidioidomycosis and Esophageal Carcinoma - Paulo Victor Alves Tubino; Bruno Jose de Queiroz Sarmento; Vitorino Modesto dos Santos; Estevão Ribeiro Borges; Lucas Evangelista Correia da Silva; Rodrigo de Souza Lima (Mycopathologia, 2012)

Higher dopamine transporter density in Parkinson’s disease patients with depression - Andre C. Felicio; Tais S. Moriyama; Clecio Godeiro-Junior; Ming C. Shih; Marcelo Q. Hoexter; Vanderci Borges; Sonia M. A. Silva; Edson Amaro-Junior; Luiz A. F. Andrade; Henrique B. Ferraz; Rodrigo A. Bressan (Psychopharmacology, 2010)

Influence of trees on soil nutrient pools in a silvopastoral system in the Brazilian Savannah - Guilherme Lanna Reis; Ângela Maria Quintão Lana; Rogério Martins Maurício; Regina Maria Quintão Lana; Rodrigo Matta Machado; Iran Borges; Talmir Quinzeiro Neto (Plant and Soil, 2010)